Método para Mensuração e Evidenciação do Environmental Debt em Sistemas Produtivos - Collatto, Dalila Cisco (Universidade do Vale do Rio dos Sinos, 2017)
The demand for greater transparency and accountability for environmental issues stems from growing social awareness of pollution damage and the debate on sustainable development. Responsible use of natural resources is an important social and political issue, and as such it is an essential factor in business decision making. In this scenario, accounting practices need to include valuation and analysis of external costs and Environmental Debts as part of the information made available to decision makers. Therefore, this study is focused on proposing a method to measure and evidence the Environmental Debt (ED) of a productive system. For this purpose, Design Science Research is used to conduct the research, whose main result makes possible to propose the Environmental Debt Measurement and Evidence Method (MEED). The method is developed from a combination of resources identified in the literature, from propositions from research groups, from consulting market methods and from international organizations involved in the recognition of the price of natural resources. The result of applying MEED reveals the valuation and disclosure of external costs and environmental obligations from the internalization of environmental externalities, linked to the primary objective of accounting, namely, valuation of equity. The method is tested in the poultry sector, specifically in the production of griller chickens, and evaluated by experts from multidisciplinary areas. Environmental externalities are present in the evaluated system, negatively affecting the equity. Finally, the Integrated Report is presented as communication tool aiming at generating information to subsidize business management, encouraging production systems to seek solutions that impact less the environment and providing better quality of life for society.
Keywords: Externalidades ambientais; Custos externos; Environmental Debt; Métodos de avaliação econômica; Contabilidade gerencial; Environmental externalities; External costs; Environmental Debt; Methods of economic evaluation; Management accounting; ACCNPQ::Engenharias::Engenharia de Produção